La inseguridad ciudadana en los espacios públicos de la urbanización Rumipamba de las rosas del cantón Salcedo modelos de gestión de seguridad, año 2018. - Coronado Orellana, Aracelly del Carmen (2020)
Citizen insecurity is the product of economic and social models that have involved developing countries in problems that become time bombs and sources of problems that affect social development. In recent years, insecurity has increased considerably, this research analyzes the level of citizen insecurity in the public spaces of the Rumipanba de las Rosas urbanization of the Salcedo canton, in order to propose a local management model that contributes to reducing this problematic.